Association of sleep traits with male fertility: a two-sample Mendelian randomization study - Lu, Shikuan; Ma, Ziyang; Zhou, Wanzhen; Zeng, Hongsen; Ma, Jian; Deng, Hang; Zhang, Peihai (Frontiers in Genetics, 2024)
Background: Previous observational studies have investigated the association between sleep-related traits and male fertility; however, conclusive evidence of a causal connection is lacking. This study aimed to explore the causal relationship between sleep and male fertility using Mendelian randomisation. Methods: Eight sleep-related traits (chronotype, sleep duration, insomnia, snoring, dozing, daytime nap, oversleeping, and undersleeping) and three descriptors representing male fertility (male infertility, abnormal sperm, and bioavailable testosterone levels) were selected from published Genome-Wide Association Studies. The causal relationship between sleep-related traits and male fertility was evaluated using multiple methods, including inverse variance weighting (IVW), weighted median, Mendelian randomisation-Egger, weighted model, and simple model through two-sample Mendelian randomisation analysis. Mendelian randomisation-Egger regression was used to assess pleiotropy, Cochrane’s Q test was employed to detect heterogeneity, and a leave-one-out sensitivity analysis was conducted. Results: Genetically-predicted chronotype (IVW,OR = 1.07; 95%CL = 1.04–1.12; p = 0.0002) was suggestively associated with bioavailable testosterone levels. However, using the IVW method, we found no evidence of a causal association between other sleep traits and male fertility. Conclusion: This study found that chronotype affects testosterone secretion levels. However, further studies are needed to explain this mechanism.